2000
DOI: 10.1139/g99-141
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal location of a Triticum timopheevii - derived powdery mildew resistance gene transferred to common wheat

Abstract: A dominant powdery mildew resistance gene introduced from Triticum timopheevii in line 146-155-T of common wheat, Triticum aestivum, was located on chromosome 6B by monosomic analysis. Restriction fragment length polymorphism (RFLP) and microsatellite analyses detected the presence of a T. timopheevii segment, translocated to chromosome 6B, with breakpoints between the loci Xpsr8/Xpsr964 on 6BS and Xpsr154/Xpsr546 on 6BL. The novel powdery mildew resistance gene, which has been designated Pm27, was shown to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Molecular markers have not only been successfully employed in determining the location of Triticum aestivum-and T. dicoccoides-derived powdery mildew resistance loci at the subchromosomal level (Hartl et al 1995(Hartl et al , 1999Huang et al 2000b;Rong et al 2000;Tao et al 2000;Liu et al 2002;Neu et al 2002), but they have also been instrumental in the genetical delimitation of alien translocation fragments harbouring powdery mildew resistance determinants: Pm13 from Aegilops longissima was mapped to a translocated3S l S segment distal to Xcdo460-3B (Cenci et al 1999), and Pm27 from T. timopheevii was pinpointed to a fragment with breakpoints between the marker loci Xpsr8/Xpsr964 on 6BS and Xpsr154/Xpsr546 on 6BL (Järve et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers have not only been successfully employed in determining the location of Triticum aestivum-and T. dicoccoides-derived powdery mildew resistance loci at the subchromosomal level (Hartl et al 1995(Hartl et al , 1999Huang et al 2000b;Rong et al 2000;Tao et al 2000;Liu et al 2002;Neu et al 2002), but they have also been instrumental in the genetical delimitation of alien translocation fragments harbouring powdery mildew resistance determinants: Pm13 from Aegilops longissima was mapped to a translocated3S l S segment distal to Xcdo460-3B (Cenci et al 1999), and Pm27 from T. timopheevii was pinpointed to a fragment with breakpoints between the marker loci Xpsr8/Xpsr964 on 6BS and Xpsr154/Xpsr546 on 6BL (Järve et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used in wheat for gene mapping. Currently, SSR markers have been successfully used in important wheat traits such as resistance to stripe rust and powdery mildew resistance gene mapping research (Jarve et al 2000;Liu et al 2002). In our laboratory, many leaf rust resistance genes such as LrZH84 (Zhao et al 2008), LrG98 (Chen et al 2010), LrXi (Li et al 2010a), LrBi16 (Zhang et al 2011), LrNJ97 (Zhou et al 2013), and LrFun (Xing et al 2014) were identified using SSR markers.…”
Section: Discussion Ssr Markersmentioning
confidence: 99%
“…Using RFLP and microsatellite analysis, a Triticum timopheevii translocation was detected in chromosome 6B of the hybrid line 146-155-T and its breakpoints were located (Järve et al, 2000). The results of the hybridization of the rDNA intergenic spacer fragment showed that the region flanking the NorB2 locus in the introgression line originated from chromosome 6G of T. timopheevii and had been transferred into 146-155-T by homoeologous recombination.…”
Section: Pm27mentioning
confidence: 97%